PENGARUH CORPORATE SOCIAL RESPONSBILITY, KEPEMILIKAN KELUARGA DAN PERENCANAAN PAJAK TERHADAP PENGHINDARAN PAJAK (TAX AVOIDANCE) - Rahmadanti Rahmadanti; Nur Sayidah (Surplus: Jurnal Riset Mahasiswa Ekonomi, Manajemen, dan Akuntansi, 2021)
The purpose of this study is to analyze the Influence of Corporate Social Responsbility, Family Ownership and Tax Planning on Tax Avoidance (Tax Avoindance). Tax Avoidance (Tax Avoindance) is a legal action, because it is done by reducing the tax burden owed by looking for existing regulatory weaknesses. Tax avoidance is considered exploitation, complexity, technicality, and loopholes in tax law. The population in this study is a company registered in Jakarta Islamic Index in 2019. The sampling method is done by purposive sampling technique. The sample in this study is a company registered in Jakarta Islamic Index in 2019 30 companies. . The results of this study showed coporate social responsibility, family ownership and tax planning simultaneously had a significant effect on tax avoidance as evidenced by a significant value of 0.013 < 0.05. Partially corporate social responsebility has a significant effect on tax avoidance this is evidenced by a significant value of 0.073 < 0.10 , family ownership has a significant effect on tax avoidance as evidenced by a significant value of 0.003 $ 0.05 and tax planning has no significant effect on tax avoidance as evidenced by a significant value of 0.22 > 0.05.